Steroidogenic Acute Regulatory Protein Expression in the Central Nervous System - King, Steven R.; Stocco, Douglas M. (Frontiers in Endocrinology, 2011)
Locally produced neurosteroids are proposed to have many functions in the central nervous system. The identification of the steroidogenic acute regulatory (StAR) protein in steroid-producing neural cells provides a new tool to understand the sites, regulation and importance of their synthesis.